Comparative analysis of bending particularities for various post-consumer wood species and age categories - Voronovich, V`yacheslav; Gayda, Serhiy (Forestry, Forest, Paper and Woodworking Industry, 2011)
The study of wood bending particularities for various wood species, age categories, specimens size and various duration of preliminary steaming indicates that the maximum bending radius is achieved by increased hydrothermal treatment duration and decrease in the cross-sectional diametre of specimens. Also it was revealed that the wood of the third age category, that is the oldest one, and, most probable, post-consumer wood is best amenable to bending. Thus, it is found that an alternative technigue for obtaining curved components can be solid wood bending. It is this technigue which makes it possible to produce curved components in furniture making with maximum wood saving. Besides, it is not improbable that post-consumer wood can be used for obtaining bent wood components because it is best suited for this process and ensures high values of bending radius. For the purpose of wood raw material saving and development of woodworking technigues, we propose that carving operations for obtaining curved components should be replaced by solid wood bending involving preliminary hydrothermal treatment.